2011
DOI: 10.3109/10641963.2010.532265
|View full text |Cite
|
Sign up to set email alerts
|

ADRB1 as a Potential Target for Gene Therapy of Pregnancy Induced Hypertension and Gestational Diabetes Mellitus

Abstract: Pregnancy-induced hypertension (PIH) and gestational diabetes mellitus (GDM) do not cause any problems with recognition; however, their pathophysiologies are still not explained. Yet many authors suggest that adrenergic β-1 receptor (ADRB1) plays a crucial role. The aim of this study was to evaluate the transcription activity of ADRB1 by using real-time polymerase chain reaction (PCR) in placenta from normal pregnancies and from PIH and GDM. Obtained findings demonstrated a significant increase in ADRB1 mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Placental transfer of amino acids is essential for fetal growth. Moreover, ADRB1 may be a novel marker for VCT, which has been established as a potential target in GDM (33). The localization of these proteins in cells was confirmed by immunofluorescence analysis (Figure 2C).…”
Section: Single-cell Transcriptome Profiling Of Trophoblast Cells In Gdmmentioning
confidence: 69%
“…Placental transfer of amino acids is essential for fetal growth. Moreover, ADRB1 may be a novel marker for VCT, which has been established as a potential target in GDM (33). The localization of these proteins in cells was confirmed by immunofluorescence analysis (Figure 2C).…”
Section: Single-cell Transcriptome Profiling Of Trophoblast Cells In Gdmmentioning
confidence: 69%
“…As we summarized in Aim 1, previous studies consistently show evidence of adrenergic receptor expression within the fetoplacental vasculature (Fig. 3), suggesting that agonist-activated adrenergic receptor pathways may alter vascular tone in the fetoplacental circulation [40,44,48,49,52,55–83].…”
Section: Methodsmentioning
confidence: 52%
“…As summarized in Figure 3 , there is evidence showing that all adrenergic receptor subtypes are expressed in the human fetoplacental vasculature. The majority of studies have been conducted using HUVECs or whole placental homogenates, and reported the expression of α 1A , α 1B , α 1D , α 2A , α 2B , α 2C [ 58 , 63 , 69 , 70 ] and β 1 , β 2 and β 3 adrenergic receptor subtypes [ 58 , 73 , 74 , 76 , 79 ], without clarifying the locus or the vessel type [ 70 , 73 , 74 , 76 ] and with a likely high background expression from trophoblast cells [ 69 ]. α 2A appears to be the only adrenergic receptor subtype identified in both endothelial cells and VSMCs within the blood vessels of stem, intermediate and terminal villi [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pink module was identified with a weak, although significant correlation to islet amyloidosis ( r = 0.3), which included 20 genes recognized as hub genes for their strong correlation to the module eigengene. Table 5 lists these genes, out of which four were previously reported in relation to T2D and pancreatic beta cells: ARDB1, FXYD3, F13A1 and FXYD2 (811). None of the module hub genes, including the four mentioned ones, have been previously associated with islet amyloidosis.…”
Section: Resultsmentioning
confidence: 99%